PUTUSAN HAKIM TERHADAP PEMBERHENTIAN APARATUR SIPIL NEGARA PENYANDANG DISABILITAS OLEH KEMENTRIAN KEUANGAN REPUBLIK INDONESIA. (NOMOR.22/G/2021/PT.TUN.JKT.) - Arini Pertiwi; Yogo Pamungkas (Reformasi Hukum Trisakti, 2023)
The Civil Servants (ASN) consist of Civil Servants and Government Employees with Employment Agreements (PPPK) within government agencies. In Indonesia, people with disabilities can become ASN. The research problem in this study is whether the termination of ASN from the Ministry of Finance of the Republic of Indonesia is in accordance with Government Regulation Number 94 of 2021 regarding the Discipline of Civil Servants and whether the court's decision is in line with Government Regulation Number 94 of 2021 on the Discipline of Civil Servants. The method used is a normative juridical approach, referring to relevant laws and regulations. Data were obtained from primary and secondary legal sources, with deductive conclusions. The research results show that disciplinary penalties against ASN are in accordance with the applicable procedures, while the court's decision that granted the ASN's lawsuit is not in accordance with Government Regulation Number 94 of 2021